Student Awareness of Costs and Benefits of Educational Decisions: Effects of an Information Campaign and Media Exposure - Martin McGuigan; Sandra McNally; Gill Wyness (Institute for the Study of Labor (IZA), 2014)
University fees have recently trebled in England, prompting fears that young people may be put off from participating in higher education. We investigate students' knowledge and their receptiveness to information campaigns about the costs and benefits of staying on in education. We compare the effects of a specially designed information campaign to the effects of media exposure about the increase in tuition fees. The latter has a stronger effect on relevant outcomes. However, we find that an inexpensive information campaign can be effective in improving information and reducing perceived financial barriers to university participation, especially for students from disadvantaged backgrounds.
Keywords: I2; 330; tuition fees; information campaign; educational decisions